2018
DOI: 10.5902/2179769229596
|View full text |Cite
|
Sign up to set email alerts
|

Práticas dos enfermeiros às pessoas em crise psíquica em decorrência do uso abusivo de drogas

Abstract: RESUMO: Objetivo: compreender as práticas dos enfermeiros em serviço de urgência e emergência às pessoas em situação de crise psíquica decorrente do uso abusivo de drogas. Método: pesquisa descritiva, abordagem qualitativa realizada com 19 enfermeiros que trabalham no pronto-socorro de um hospital geral no interior do Rio Grande do Norte. Os dados foram coletados através de uma entrevista semiestruturada, e após foram submetidos à análise de conteúdo. Resultados: os enfermeiros enfatizam que suas práticas são … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The authors point out that insecurity, fear and vulnerability limit the performance of these professionals and showed significant limitation of knowledge with regard to the resolution of crises. Lima et al (2018) showed that nurses value the complaint of the companion more in relation to that of the patient himself, reinforcing the dehumanization in the care provided. The professionals did not believe that listening could be an instrument of nursing practice in the emergency and emergency services, attributing this responsibility to social service and psychology professionals (LIMA et al, 2018;FERNANDES et al, 2016;KONDO et al, 2011).…”
Section: Knowledge Of Nurses Working In the Emergencies Of General Ho...mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors point out that insecurity, fear and vulnerability limit the performance of these professionals and showed significant limitation of knowledge with regard to the resolution of crises. Lima et al (2018) showed that nurses value the complaint of the companion more in relation to that of the patient himself, reinforcing the dehumanization in the care provided. The professionals did not believe that listening could be an instrument of nursing practice in the emergency and emergency services, attributing this responsibility to social service and psychology professionals (LIMA et al, 2018;FERNANDES et al, 2016;KONDO et al, 2011).…”
Section: Knowledge Of Nurses Working In the Emergencies Of General Ho...mentioning
confidence: 99%
“…In the study by Lima et al (2018) the nurses suggested the creation of a specific sector in the emergency room, with psychiatric beds, to better structure and pay attention to these patients in crisis and the recognition of a prioritized care in the needs of patients.…”
Section: Strategies To Increase the Level Of Knowledge Of Nurses In G...mentioning
confidence: 99%